If have the same numerator but different denominators which one is greater

Answers

Answer 1
Answer: The one with the lowest denominator.
Answer 2
Answer: the one with the lowest denominator 

Related Questions

jimmy has a pocket full of nickels ans quarters. there are a total of 50 coins. when he added it all up he had $5.30. how many nickels did he have?
Jason and his 3 roommates share the cost of the electric bill evenly
How is 0.80 greater and 0.8 smaller please be as detailed as you can :) Stretch your thinking always gets me :)
Find the value of x in the triangle. Then classify the triangle as acute, right, or obtuse.(image) a. 93°, acute c. 108°, acute b. 98°, obtuse d. 97°, right
Please help with mathematics

Which value for x makes the sentence true?13x - 8x = 10

A.3
B.2
C.4
D.8

question from study island

Answers

Subtract 8x from 13x to get 5x.
5x=10

Divide each term in the equation by 5.
5x/5=10/5 

x=10/5 

Divide 10 by 5 to get 2. 

x=2

1_9,644=100,000 to the nearest ten thousand

Answers

119,644 is the answer I believe

What is the solution of the system of linear equations? y=3/2 x+1 and y=3/4 x-2

Answers

Answer:

(-4,-5)

y= -5

x= -4

Step-by-step explanation:

y=3/2x+1

y=3/4x-2

solve using the comparison method

3/2x+1=3/4x-2

subtract 3/2 from both sides

-3/4x+1=-2

subtract 1 from both sides

3/4x=-3

divide both sides by 3/4

x= -4

substitute the value of x into an equation

y=3/2(-4)+1

distribute

y= -6+1

add, but 6 is negative so subtract

y= -5

-------------

(-4,-5)

-------------

Jones only tree school has 540 students 70% of these students walk to school how many students walk to school

Answers

1.) 540 ( 70 percent )

2.) 540 ( 0.7 )

3.) 54 ( 7 )

4.) 378

Answer:

The correct answer would be 378

Step-by-step explanation:

^w^

Which ordered pair is the solution to the system of equations? A. (1, 7)
B. (4, 9)
C. (7, 19)
D. (8, 21)

Answers

I could just give you the answer but you should know how so you don't need my help :)

Solve by substitution.

Step 1: Set the first equation to y by isolating the y term.

2x-y=-5
2x+5=y (see how that worked? I flipped the signs of the numbers and moved them)

Step 2: Substitute the new equation for y in the second equation.

x+3y=22 -> x+3(2x+5)=22 (now lets simplify)
7x+15=22 (I distributed and added like terms) (now we can isolate that pesky x term)
7x=7 (now its trickier than just flipping the sign, now i have to divide x by 7 since it is multiplied by 7)
x=1

Step 3; Substitute the new x answer into the original first equation

2x-y=-5 -> 2(1)-y=-5 (Lets isolate now since we already know that 2x1 is 2.)
-y=-7 (lets cancel out those signs to finish the isolation)
y=7

So your answer is 1,7

If f(x) = 3x2 - 4 and g(x) = x +2, find (f-g)(x)​

Answers

Answer:

3x^2 -x-6

Step-by-step explanation:

If f(x) = 3x^2 - 4 and g(x) = x +2

(f-g)(x)​

I like to line them up vertically

3x^2       - 4

       -( x +2)

----------------------

Distribute the minus sign

3x^2       - 4

          - x -2

----------------------

3x^2 -x-6